Translation Studies and Film Studies as Interdisciplinary Disciplines - Gayathree, S. (University of Jaffna, 2023)
Translation Studies is always interdisciplinary in nature as different disciplines try to own it up and claim it as their realm and it goes beyond the boundaries and its place keeps changing. In a way, Translation Studies is situated at the crossing lines as the assumed boundaries of many disciplines. The interdisciplinarity of Translation Studies with Film Studies could be featured in many ways. Both Translation and Film focus on how people perceive the product. This paper observes some interrelationships between Translation Studies and Film Studies and describes the correlation by citing some instances. Some general observations are pinpointed regarding the interdisciplinary nature of Translation Studies with Film Studies. The observations are helpful in identifying various scopes and indispensable demands for translation. The relationships are discussed by classifying the process and the classification systematically clusters the types of translations practiced.
Keywords: Interdisciplinary; Translation studies; Film studies; Process; Product